The 2nd International Symposium of Primo-vascular System (Medical Association of Pharmacopuncture Institute, 2021)
Fu's subcutaneous needling (FSN) is a novel acupuncture approach. Although it has been popularized and widely used by acupuncture practitioners, theoretical research on its mechanism of action remains lacking. This study establishes an immunological hypothesis for the efficacy of FSN basis existing knowledge in biomedical science, histology and physiology, and traditional acupuncture mechanisms. The theoretical inference indicates that FSN treatment may affect the body's immune system through subcutaneous connective tissue, similar to triggering a cobweb-like system. This article also proposes possible clinical implications of this theory, which require further studies to validate.